MONETARY POLICY VOLATILITY AND PERFORMANCE OF BANKING INDUSTRY IN NIGERIA: SIGNS FROM THE COVID-19 PANDEMIC (Malaysian Management Journal, 2022)
Health volatility due to the Covid-19 pandemic presented a new-fangled trial to the banking industry with a spillover effect of monetary policy volatility, which extremely affected the performance of the banking industry in Nigeria. It has become a matter of concern to assess monetary policy volatility and performance of the banking industry in Nigeria. The paper used annual time series data that spanned the period of 2008 to 2020. The paper employed Autoregressive Distributed Lag (ARDL) and Exponential Generalized Autoregressive Conditional Heteroskedasticity (EGARCH) as its techniques of estimation. Based on the ARDL result, it was exposed that monetary policy volatility had a negative impact on the activities of the banking industry in Nigeria within the study time. In addition, according to the EGARCH test result, the paper generalized that monetary policy volatility had constantly been accompanied by a new volatility. Therefore, as a result of the universal financial predicament experienced in 2008, this caused a higher monetary policy volatility in 2020 in the face of Covid-19. The paper observed that a rise in monetary policy volatility led to a decline in the performance of the banking industry in Nigeria within the study period, and the current monetary policy volatility led to its uncertain volatility in the period ahead. The paper recommended based on the findings that banks through the Central Bank of Nigeria should employ tactical monetary policy strategies to reduce monetary policy volatility during the Covid-19 pandemic toward enhancing the performance of Nigeria’s banking industry.